2011
DOI: 10.1007/s10534-011-9478-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uranium (U) on the cellular glutathione pool and resultant consequences for the redox status of U

Abstract: Uranium (U) as a redox-active heavy metal can cause various redox imbalances in plant cells. Measurements of the cellular glutathione/glutathione disulfide (GSH/GSSG) by HPLC after cellular U contact revealed an interference with this essential redox couple. The GSH content remained unaffected by 10 μM U whereas the GSSG level immediately increased. In contrast, higher U concentrations (50 μM) drastically raised both forms. Using the Nernst equation, it was possible to calculate the half-cell reduction potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The fact that GSH and oxidized GSH (GSSG) levels are increased in uranyl-supplemented cultures of plant cells (26) or hepatocytes (27) is a strong indication that GSH is also involved in uranyl detoxification in higher organisms, in which uranyl toxicity has been related to oxidative stress (1). Although consistent with uranyl-induced GSH production, mechanisms other than ROS suppression by GSH-dependent detoxification need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that GSH and oxidized GSH (GSSG) levels are increased in uranyl-supplemented cultures of plant cells (26) or hepatocytes (27) is a strong indication that GSH is also involved in uranyl detoxification in higher organisms, in which uranyl toxicity has been related to oxidative stress (1). Although consistent with uranyl-induced GSH production, mechanisms other than ROS suppression by GSH-dependent detoxification need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of uranium has been linked to oxidative stress, as deduced from effects on intracellular GSH levels in plants (24,25). It has been shown that uranyl affects the levels of both GSH and its oxidized form, GSSG, in cultured plant cells (26) and animals (27). However, the effect of uranyl on GSH levels is not uniform among the tested model organisms and cell cultures, nor does the GSH level vary in proportion to the uranyl concentration within a given system.…”
mentioning
confidence: 99%
“…(Vandenhove et al 2006) found altered levels of the glutathione pool depending on the applied uranium concentrations in Phaseolus vulgaris after a week of exposure. Concerning the initial phase of metal contact (up to 24 hours), there was no significant change of GSH whereas the amount of GSSG increased upon exposure of moderate uranium concentrations (≤ 10 μM) in cell suspensions of canola ( Brassica napus ) (Viehweger et al 2011. This indicates clearly its function as redox couple (E pH7.4 ;Schafer and Buettner  = −264 mV at 25°C, Schafer and Buettner Schafer and Buettner 2001) and underlines the consumption of cellular reducing capacity during heavy metal accumulation and causes oxidative stress.…”
Section: Heavy Metal Tolerance and Toxicity On Cellular Levelmentioning
confidence: 99%
“…An increase in the antioxidative metabolites after heavy metal exposure has been observed before by Vanhoudt et al [ 15 ]. In addition, exposing a cell culture of Brassica napus to 50 µM U resulted in a significant increase in GSH concentration [ 45 ]. Finally, Aranjuelo et al [ 46 ] observed in glutathione deficient Arabidopsis mutants ( cad2.1 ) the highest MDA and least reduced ascorbate levels, which highlights the importance of GSH under U stress.…”
Section: Discussionmentioning
confidence: 99%